NanoXplore wins graphene order from Martinrea for fuel and brake lines in passenger vehicles. Issue 12 (December 2020) - Unknown
Abstract : In Canada, Montreal-based NanoXplore has received a blanket purchase order from Martinrea International in Ontario to supply graphene for fuel and brake lines for passenger vehicles produced by North American automotive original equipment manufacturers (OEMs).